An analysis of calibration and discrimination among multiple cardiovascular risk scores in a modern multiethnic cohort - DeFilippis, Andrew P; Young, Rebekah; Carrubba, Christopher J; McEvoy, John W; Budoff, Matthew J; Blumenthal, Roger S; Kronmal, Richard A; McClelland, Robyn L; Nasir, Khurram; Blaha, Michael J (Annals of internal medicine, 2015)
Accurate risk assessment of atherosclerotic cardiovascular disease (ASCVD) is essential to effectively balance the risks and benefits of therapy for primary prevention. To compare the calibration and discrimination of the new American Heart Association (AHA) and American College of Cardiology (ACC) ASCVD risk score with alternative risk scores and to explore preventive therapy as a cause of the reported risk overestimation using the AHA-ACC-ASCVD score. Prospective epidemiologic study of ASCVD. MESA (Multi-Ethnic Study of Atherosclerosis), a community-based, sex-balanced, multiethnic cohort. 4227 MESA participants aged 50 to 74 years and without diabetes at baseline. Observed and expected events for the AHA-ACC-ASCVD score were compared with 4 commonly used risk scores-and their respective end points-in MESA after a 10.2-year follow-up. The new AHA-ACC-ASCVD and 3 older Framingham-based risk scores overestimated cardiovascular events by 37% to 154% in men and 8% to 67% in women. Overestimation was noted throughout the continuum of risk. In contrast, the Reynolds Risk Score overestimated risk by 9% in men but underestimated risk by 21% in women. Aspirin, lipid-lowering or antihypertensive therapy, and interim revascularization did not explain the overestimation. Comparability of MESA with target populations for primary prevention and possibility of missed events in MESA. Of the 5 risk scores, 4, including the new AHA-ACC-ASCVD score, showed overestimation of risk (25% to 115%) in a modern, multiethnic cohort without baseline clinical ASCVD. If validated, overestimation of ASCVD risk may have substantial implications for individual patients and the health care system. National Heart, Lung, and Blood Institute.